High Expression of PARP1 in Tumor and Stroma Cells Predicts Different Prognosis and Platinum Resistance in Patients With Advanced Epithelial Ovarian Cancer - Zuo, Wei-Wei; Zhao, Chun-Fang; Li, Yan; Sun, Hai-Yan; Ma, Guo-Ming; Liu, Yue-Ping; Kang, Shan (Frontiers in Oncology, 2022)
Objective This study aimed to explore the roles of PARP1 mRNA and protein expression in platinum resistance and prognosis of EOC patients, and reveal the different roles of PARP1 protein in epithelial tumor and stroma cells. Methods The PARP1 mRNA expression of the EOC tissues was examined by RT-qPCR. The impacts of PARP1 expression on prognosis were measured by Kaplan-Meier and Cox regression. Receiver operating characteristic (ROC) curve analysis was employed for calculating the diagnostic value of PARP1 on platinum resistance. The microarray of formalin-fixed, paraffin-embedded (FFPE) tissues was processed for multiplex immunofluorescence to detect the protein levels of PARP1 and cytokeratin (CK). Results The PARP1mRNA expression of EOC patients was higher in the platinum-resistant group compared with the sensitive group (P<0.01). Kaplan-Meier analysis demonstrated that high PARP1 mRNA expression was associated with poor survival of EOC patients. In Cox regression analyses, high PARP1 mRNA expression independently predicted poor prognosis (P=0.001, HR=2.076, 95%CI=1.373-3.140). The area under the ROC curve of PARP1 mRNA for predicting the platinum resistance in EOC patients was 0.649, with a sensitivity of 0.607 and specificity of 0.668. Furthermore, the protein expression of PARP1 was higher in the platinum-resistant group than in the sensitive group (P<0.01) and associated with a worse prognosis. Additionally, according to CK labeling, we observed that enhanced expression of PARP1 in the CK+ region was associated with platinum resistance and lower survival, but in CK- region, it predicted a good prognosis and platinum sensitivity. Conclusion PARP1 may be a potential biomarker to predict platinum resistance and prognosis for EOC patients, exerting different roles on epithelial tumor and stromal cells.